2009
DOI: 10.1111/j.1478-5153.2008.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory weaning: a case study of protracted weaning

Abstract: This reflective analysis highlights the benefits and importance of the nurse-patient relationship during what was a very protracted ventilatory wean. This shared trajectory enabled significant patient empowerment, and this case study gives the patient the voice she temporarily lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
1
8
0
5
Order By: Relevance
“…For ISV diagnosis, the characteristics dyspnea, increased agitation, decreased cooperation, increased heart rate and accessory muscle use, justified the inference of diagnosis, similar to our findings (19) . With regard to the relationship of the related factors to nursing diagnoses, a study found that bronchial secretions and retained secretions influenced by approximately 11 times the occurrence of IBP, and about three times IGE (16) .…”
Section: Discussionsupporting
confidence: 89%
“…For ISV diagnosis, the characteristics dyspnea, increased agitation, decreased cooperation, increased heart rate and accessory muscle use, justified the inference of diagnosis, similar to our findings (19) . With regard to the relationship of the related factors to nursing diagnoses, a study found that bronchial secretions and retained secretions influenced by approximately 11 times the occurrence of IBP, and about three times IGE (16) .…”
Section: Discussionsupporting
confidence: 89%
“…Most reviews of weaning from mechanical ventilation have examined only quantitative data [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Range of health care professionals [25][26][27][28][29][30][31][32][33][34][35] Patients only [36][37][38][39][40][41][42][43][44][45] Physicians only (intensivists or anesthetists working in intensive care units) [46][47][48][49] Patients' family members 50,51 Patients and nurses Participant interviews and observation 12,13,27,28,[31][32][33]40<...>…”
Section: Discussionmentioning
confidence: 99%
“…Thematic content analysis Grounded theory [17][18][19]21,34,39,41 Case study 26,42 Unclear 33 15 (35) 11 (26) 10 (23) 4 (9) 2 (5) 1 (2) 10 (23) 10 (23) 9 (21) 7 (16) 3 (7) 4 (9) 25 (58) 8 (19) 6 (14) 3 (7) 1 (2) 15 (35) 10 (23) for decision making or use of weaning protocols and guidelines. This characteristic made interpretive synthesis difficult, and thus we opted to generate a narrative summary to comprehensively map knowledge provided by the included studies.…”
Section: Methodsmentioning
confidence: 99%
“…In the first year of the journal, clinician‐authored papers tended to focus on matters such as: providing counselling in intensive care unit (ICU) (Mellish 1996), using intracranial pressure (ICP) monitoring (Odell 1996) and changing practice to primary nursing (Bray 1996). In 2009, clinicians are writing highly complex and conceptual papers, for example the reflective analysis of using nursing diagnoses to manage problems related to weaning (Pattison and Watson 2009) and the systematic review of anticoagulant therapy in critically ill patients undergoing continuous renal replacement therapy (Tillman 2009). The development of free online resources for academic writing is helpful for clinicians, students and supervisors, for example the Online Writing Lab (OWL) at Purdue, see http://owl.english.purdue.edu/owl/ (accessed 13/10/09), which also has useful sections for those who have English as a second (or additional) language.…”
Section: Authorshipmentioning
confidence: 99%